Comment: Leadership and Language - Urwick, L. (Academy of Management Journal, 1965)
The article discusses the managerial style and effective communication of Sir Winston Spencer Churchill as evidenced through the broadcasts that he made throughout 1940, when Great Britain faced air attacks and a threatened invasion by Germany. The article focuses particularly on the language used by Churchill in his speeches, which was succinct, simple, and yet inspiring to the British people. The author draws a parallel to the necessities of business communications, which have become increasingly complex and more difficult to understand. The author encourages teachers of business to teach their students to write simply and clearly in order to communicate valuable ideas which do not necessitate dressing of complex terminology.